The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/frfst.2023.1157649
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-life extension of traditional licorice root “sherbet” with a novel pulsed electric field processing

Abstract: Pulsed electric field (PEF) processing of licorice root “sherbet” (LRS) by various electric field strengths (7.00, 15.50, and 24.10 kV/cm), treatment times (108, 432, and 756 µsec), and processing temperatures (6, 18, and 30°C) according to the Box–Behnken design were performed. The samples were analyzed for pH, titratable acidity, conductivity, turbidity, total reducing sugar, color (L*, a*, and b*), hue, chroma, total color difference, color intensity, color tone (yellow, red, and blue color tones), total an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In an opposite study, Machado et al (2019) found that the antioxidant activity, determined by the DPPH method, in probiotic juçara and banana sorbet during −20 °C storage showed a significant increase [ 65 ]. Also, Evrendilek et al (2023) detected that the antioxidant capacity of the pulsed electric field-treated (6.90 kV/cm, 756.00 µs, and 7.48 °C) licorice root sherbet samples at 4 °C did not significantly change within the 40th-day storage [ 66 ]. In a study by Güler (2021) to determine the usability of sour grape concentrate in beverages, it was observed that the DPPH inhibition percentage decreased in the beverage with added sour grape concentrate after a 6-month storage period at 4 °C [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…In an opposite study, Machado et al (2019) found that the antioxidant activity, determined by the DPPH method, in probiotic juçara and banana sorbet during −20 °C storage showed a significant increase [ 65 ]. Also, Evrendilek et al (2023) detected that the antioxidant capacity of the pulsed electric field-treated (6.90 kV/cm, 756.00 µs, and 7.48 °C) licorice root sherbet samples at 4 °C did not significantly change within the 40th-day storage [ 66 ]. In a study by Güler (2021) to determine the usability of sour grape concentrate in beverages, it was observed that the DPPH inhibition percentage decreased in the beverage with added sour grape concentrate after a 6-month storage period at 4 °C [ 67 ].…”
Section: Resultsmentioning
confidence: 99%